PROBLEMS IN PERMENKUMHAM NO. 34 OF 2017 RELATING TO CHANGES IN THE MANAGEMENT OF POLITICAL PARTIES IN CIRCUMSTANCES OF INTERNAL DISPUTE - Dwi Darojatun Patra Suwito (Jurnal Ilmiah Advokasi, 2024)
Political parties are main players in competing for and maintain power legally in democratic countries. As a power oriented organization, a political party also has risk of internal dispute and schism. Law Number 2 of 2011 regulate the space for the internal dispute settlement, namely through internal party court and judicial institution. In dispute relating to organization structure, verdicts issued by the internal party court and judicial institution need to be followed by the issuance of ratification decision letter from the Minister of Law and Human Rights.This research used the type of doctrinal research. The data source that is used in this research is library study technique. Analysis of the data used is by using qualitative methods.Based on the result of this research, it can be concluded that Minister of Law and Human Rights Number 34 of 2017 has a lack of regulation regarding the change of political party organization structure in internal dispute circumstance. This lack of regulation can cause legal uncertainty and can obstruct political parties in obtaining decision of organization structure ratification form Minister of Law and Human Rights.Â Keywords: Internal dispute, pollical party, Minister of Law and Human Rights.